Multiresponsive MXene Actuators with Asymmetric Quantum‐Confined Superfluidic Structures - Ma, Jia‐Nan; Ma, Bo; Wang, Zheng‐Xiao; Song, Pu; Han, Dong‐Dong; Zhang, Yong‐Lai (Advanced functional materials, 2024)
MXene, which is known for its high electrical/thermal conductivity, surface hydrophilicity, excellent mechanical flexibility, and chemical stability, is a versatile and smart material for soft actuators. However, most MXene actuators are fabricated by combining MXene with other inert materials to form a bilayer or multilayer structure. Considering the strain mismatch at multimaterial interfaces under frequent deformation, MXene‐based actuators are generally associated with poor stability, which limits their practical applications. Herein, inspired by the natural quantum‐confined superfluidic (QSF) effect, a multiresponsive MXene actuator that can be driven by moisture, light, and electricity by engineering an asymmetric QSF structure on both sides of the MXene film is reported. The actuation mechanism of the MXene film can be attributed to nonuniform water adsorption, transport, and desorption within the asymmetric QSF channels under moisture, photothermal, and electrothermal stimuli. Interestingly, MXene actuators can be flexibly formed into various shapes under moisture‐assisted mechanical compression, which not only enhances their multiresponsive actuation, but also permits a more complex deformation. As proof‐of‐concept demonstrations, various intriguing applications including a dual‐role robot, a smart shielding curtain, and a dragonfly robot, are fabricated, revealing the potential of MXene actuators for soft robotics. The multiresponsive MXene actuators with asymmetric quantum‐confined superfluidic (QSF) structures are reported for robotic applications. The actuation mechanism of the MXene film can be attributed to nonuniform water adsorption, transport, and desorption within asymmetric QSF channels. As a proof of concept, smart devices, such as a dual‐role robot, a smart shielding curtain, and a dragonfly robot, are fabricated and demonstrated.